2022
DOI: 10.1007/s00784-022-04631-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of periodontal therapy, with inflammatory biomarkers and complications in COVID-19 patients: a case control study

Abstract: Background In previous studies, COVID-19 complications were reported to be associated with periodontitis. Accordingly, this study was designed to test the hypothesis that a history of periodontal therapy could be associated with lower risk of COVID-19 complications. Methods A case–control study was performed using the medical health records of COVID-19 patients in the State of Qatar between March 2020 and February 2021 and dental records between January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 64 publications
(71 reference statements)
0
28
0
Order By: Relevance
“…Another observational study demonstrated that periodontitis posed a similar risk for COVID-19 complications as well as diabetes and hypertension, as periodontitis patients were 3 times more likely to have COVID-19 complications compared to non-periodontitis patients (p = 0.025), while diabetes and hypertension patients were 3.5 times more likely to have COVID-19 complications [10].…”
Section: Description Of the State Of Knowledgementioning
confidence: 99%
“…Another observational study demonstrated that periodontitis posed a similar risk for COVID-19 complications as well as diabetes and hypertension, as periodontitis patients were 3 times more likely to have COVID-19 complications compared to non-periodontitis patients (p = 0.025), while diabetes and hypertension patients were 3.5 times more likely to have COVID-19 complications [10].…”
Section: Description Of the State Of Knowledgementioning
confidence: 99%
“…This could be due to the differences in study design (case-control vs. prospective) and settings (hospital-based vs. community). On balance, the existing literature suggests that while severity of COVID-19 infection may be positively associated with oral health indicators including PD (14)(15)(16)(17)(18)(19), the occurrence of COVID-19 may be unrelated to oral health (13). One of the largest available studies, examined retrospective UK Biobank data on oral health status from 13,253 adults and also reported no association between poor oral health (loose teeth or painful, bleeding gums) and risk of COVID-19 infection.…”
Section: Exposurementioning
confidence: 99%
“…Despite reporting statistically significant results, the wide confidence intervals indicate low precision due to small sample size. Other limitations of these studies include convenience sampling, relative paucity of prospective data, lack of data from clinical oral examinations, and limited information on recent access to oral care (Supplementary Table S2, [12][13][14][15][16][17][18][19][39][40][41][42][43]. Additionally, only one of the previous studies had a representative population-based sample (13) and sample for most studies comprised of COVID-19 positive cases to explore the association with severity rather than risk (14)(15)(16)(17)(18)(19).…”
Section: Exposurementioning
confidence: 99%
See 2 more Smart Citations